Complicated acute myocardial infarction with simultaneous occlusion of two coronary arteries. Issue 3 (30th January 2020) - Nordkin, Irina; Goldberg, Alexander; Israeli, Zeev; Halabi, Majdi
Abstract: Simultaneous occlusion of two coronary arteries in acute MI is infrequent and may be accompanied by cardiogenic shock. Prompt restoration of normal coronary flow can salvage the myocardium and decrease a possible risk of death from complications. Abstract : Simultaneous occlusion of two coronary arteries in acute MI is infrequent and may be accompanied by cardiogenic shock. Prompt restoration of normal coronary flow can salvage the myocardium and decrease a possible risk of death from complications.